Avaliação de fatores intervenientes na formação de trialometanos em sistemas de abastecimento de água: estudo de caso na região metropolitana de Belo Horizonte - MG - Leonardo Augusto dos Santos (2013)
This study aimed to evaluate the concentration of trihalomethane in finished drinking water, from the analysis of ten water supply systems in the metropolitan region of Belo Horizonte (RMBH) to consider systems that rely on catchment water source in river or reservoir with water treatment plant (WTP) large, medium and small, with the reference flow. The raw and treated water samples were collected with fortnightly for the period from October/2012 to april/2013. Characterization of raw water was carried through the physicochemical parameters pH, temperature, turbidity, apparent color and total organic carbon (TOC). Then, the raw water was used in the trihalomethane potential formation (THMPF ) test. In the treated water were collected two samples at the output of the ETA (AT) for the characterization of trihalomethanes , and one of the samples were used in the simulation of the edge network distribution system ( RD ) , taking advantage of the contact time of 24 hours, trihalomethanes being quantified by GC - MS chromatography "purge and trap" . The Spearman correlation matrices, by means of which we investigated the correlations between trihalomethane formation potential and the variables that influence their formation, indicated that the monitored parameters (pH, temperature, turbidity, apparent color and TOC) often showed no statistically significant correlation coefficients with the potential formation of trihalomethanes. The PFTHM in all systems was greater than the concentration sampled AT and RD, noting that the contact time increased the formation of THM as can be seen in comparison between the samples AT and RD. Among the quantified trihalomethanes, chloroform showed the highest concentration in all samples . The PFTHM was observed at concentrations higher than the maximum value allowed in the current Brazilian potability standard of 0.1 mg/L, the systems Brumadinho, Rio das Velhas, Vargem das Flores and Florestal. For samples of AT and RD none of the systems had concentrations above the limit of Ordinance 2914/2011.